Implementasi Desain Interaksi pada Alat Ukur Berat dan Panjang untuk Menentukan Status Gizi Bayi - Erdano Sedya Dwiprasajawara; Mochammad Hannats Hanafi Ichsan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
A good nutritional status of infants will support their growth and development. One of the most important ways to monitor the nutritional status of infants is to know their lenght and weight nutritional status. To simplify the process of classifying the nutritional status of infants, this research will be made a device that can measure the nutritional status of infants by applying the principles of interaction design so that a device can match what the user needs, easing the user, and provide the comfort for user when it being used. This baby's nutritional measurement device using Arduino uno for processing the data and has several input function to enter baby's age and sex by using the keypad, measuring length and weight of infant by using ultrasonic sensor and load cell sensor, and ouput function in the form of result of classification of nutrient status and baby's weight on the LCD screen. On the device performance obtained average duration of 31.80 seconds to complete the entire process of nutritional status measurement. The interaction design of baby scales was tested using several usability principles that are leranability and robustness which get an average value of 4 which means agree from the likert scale 1-5 on the questionnaire, it can be concluded that this tool has a high level of usability.